FINANCIAL SECURITY OF THE STOCK EXCHANGE MARKET IN THE SYSTEM OF FINANCIAL SECURITY OF THE STATE - Holovach, M. (Socio-economic relations in the digital society, 2021)
The article examines the role of the stock exchange market in ensuring the financial security of the State, its integration into the world economic space. The main focus of the article was concentrated on the domestic government bond market, as this stock exchange market accounts for 95% of the total stock exchange market in Ukraine. Have been proved the necessity of studying the financial security of the domestic government bond market. Emphasis is placed on the connection of financial security of the stock exchange market with investment, debt security of the state and financial security of legal entities and individuals. The approaches proposed to determine the issue of financial security of the stock exchange market and its external and internal components are considered. Also, I analyzed external and internal threats that may affect the securities market in Ukraine. The data of the primary and secondary market of domestic government bonds and fluctuations of the hryvnia exchange rate against foreign currencies were studied. An analyzed the relationship between the obtained data on the markets of primary placement of domestic government bonds, their secondary sale and exchange rate fluctuations of the hryvnia against the US dollar over a two-month period and negative external factors on the financial security of stock exchange in this range. Have been made an assessment of the financial security of the domestic government bond market from external factors in Ukraine. Have been studied the probable negative scenarios that would have an impact on the national economy in the event of repeated or continuous action of these negative external factors on the domestic government bond market. Have been clarified which subjects need to pay more attention to the issue raised in the article and suggested in which direction the Ministry of Finance of Ukraine, the National Bank of Ukraine and scientists should cooperate.